Nitrogen and Soil Moisture Optimization for Tomato Crops in Semi-Arid Areas of Ethiopia - Abera Tesfaye; Tatek Wondimu; Ketema Tezera; Gebeyehu Ashemi; Tigist Worku; Aynalem Gurms (Air, Soil and Water Research)
The productivity and quality of tomato crops are influenced by nutrient management and soil moisture levels. A study was conducted in Melkassa to find the best nitrogen fertilizer rate and soil moisture level for tomato crops. The experiment employed a split-plot design and was replicated three times. The combined impact of soil moisture and nitrogen levels greatly affects the height, branch count, fruit size, fruit length, marketable yield of tomatoes, tomato fruit quality, nitrogen use efficiency and water use efficiency ( p  < .05). The optimal combination of 75% ETc and 230 kg/ha resulted in the tallest tomato plant height and the highest branch number. The highest diameter and length of tomato fruits were obtained when 75% ETc and 184 kg/ha were combined. The highest marketable tomato yields were achieved by the interaction of 75% ETc and 184 kg/ha N. Applying 50% ETc with 184 and 138 kg/ha resulted in higher WUE. Interaction of 92 kg/h and soil moisture at all levels results in the maximum AUE. The maximum PFP obtained from 138 and 184 kg/ha with no significant difference. Excessive nitrogen rates (>184 kg/ha) did not increase tomato yield and WUE except for plant height and branch number. In general, the application of 75% ETc and 138 to 184 kg/ha of nitrogen is optimal for tomato production considering the measured parameter to improve water use efficiency and nutrient management in arid and semi-arid environment. The results gave valuable information and direction for the use of organic nitrogen and water in tomato production.